Some Fundamental Problems and Opportunities From the Standpoint of Rational Agency - Horvitz, Eric (1989)
Growing enthusiasm about the application of autonomous reasoning in high-stakes domains like medicine and aerospace has stimulated interest in systems that behave in accordance with a coherent theory of rationality. Within such domains, the losses associated with suboptimal decisions tend to render simple satisfying approaches inadequate and to provide incentive for attempting to optimize the utility of computational activity. In pursuing research on rational agency over the last several years, a number of problems have come to be highlighted as rich areas for future research. In this paper, we review promising prospects for future study. The research topics will be motivated by recent research and preliminary theoretical and empirical results.
To appear in the Proceedings of the 2013 Marktoberdorf Summer School